2013
DOI: 10.1055/s-0033-1341407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obesity and Morbid Obesity on Outcomes in TKA

Abstract: The negative effects of obesity following total joint arthroplasty, such as increased morbidity and mortality, have been well documented in literature. However, little is known about whether specific body mass indices can be used as cutoffs to determine which patients are most at risk for having a poor postoperative outcome. We evaluated the effects of differing levels of obesity as measured by body mass index (BMI) on implant survivorship, Knee Society scores, complications, and radiographic outcomes. A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 22 publications
2
109
0
3
Order By: Relevance
“…We attribute this difference to the degree of obesity and the limited number of patients who were super obese. Some prior studies on obesity did not report super obesity as a separate category [1,17], and were based on a limited population (41 and 1617 respectively) or defined morbid obesity as a BMI greater than 35 kg/m 2 [5,18]. Michalka et al [18] reported on operative time, blood loss, suboptimal implant placement, the surgeons' perception of operative difficulty, and the six-minute walk test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute this difference to the degree of obesity and the limited number of patients who were super obese. Some prior studies on obesity did not report super obesity as a separate category [1,17], and were based on a limited population (41 and 1617 respectively) or defined morbid obesity as a BMI greater than 35 kg/m 2 [5,18]. Michalka et al [18] reported on operative time, blood loss, suboptimal implant placement, the surgeons' perception of operative difficulty, and the six-minute walk test.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy regarding whether obesity poses additional complications and costs with THA [7,20,28]. Some studies have reported that the risk of postoperative complications after joint arthroplasty in patients who are obese is comparable to the risk in patients who are nonobese as long as their BMI is less than 40 kg/m 2 [1,17]. However, morbid obesity is associated with a higher risk of postoperative complications [6,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…In our series, pain at the proximal aspect (defined as the area between the joint line and the 5 cm above) of the tibia was analyzed postoperatively. Pain has been evaluated after TKA in patients with obesity but to our knowledge, the proximal tibial pain that we evaluated has not been studied by others [4,12,[15][16][17]23]. In a previous report, obesity was not associated with a higher risk of moderate to severe pain in patients undergoing primary TKA at 2-or 5-year followup [4].…”
Section: Discussionmentioning
confidence: 95%
“…Previously published papers regarding BMI and pain after TKA reported controversial results [6,14,[17][18][19]24]. Most previous studies have examined the association of BMI with summary scores (not pain) [4,12,[15][16][17]23], mostly using the KSS total and objective/subjective scores and most reporting lack of an association, whereas few were positive. In one study, however, analyzing the results of 67 patients undergoing TKA for an association of obesity with pain outcomes [17], BMI of 35 to 40 kg/m 2 was associated with higher pain scores in multivariable-adjusted models that included age, gender, and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantage is to identify an organism not identified through preoperative aspiration. The disadvantage is that patients are deprived of the benefit of antimicrobial prophylaxis before skin incision, a benefit that has been called the greatest single contribution to minimizing infection in total joint arthroplasties [13,14], especially in revisions where infection rates can range from 5% to 10%, and has been documented as much as 40% in different studies [12,15,21]. This risk discrepancy is likely multifactorial, but withholding antimicrobial prophylaxis until after cultures are obtained intraoperatively may contribute to the higher rates of PJIs observed in patients undergoing revision arthroplasties.…”
Section: Discussionmentioning
confidence: 99%